Influential Article Review - Establishing the Links Between TMT Social Capital, Network Position and Innovation - Garcia, Nina; Arnold, Santiago; Harrington, Kim (Journal of Strategic Innovation and Sustainability, 2019)
This paper examines innovation. We present insights from a highly influential paper. Here are the highlights from this paper: Employing a sample of 1476 firms and 5130 firm-years in China, we examine the relationship between social capital and macro organizational innovation. Based on the relational view and social capital theory, this study investigates how the top management team (TMT) inside an organization bridges and bonds social capital to influence innovations combined with organizational network position. Through empirical tests based on listed companies in the whole network of the interlocking directorate using the dataset of listed companies in China from 2008 to 2014, the study finds that: (1) TMT global social capital has an essential positive effect on innovation, (2) TMT overseas social capital has significant positive consequences on prestige and power (network position), (3) network position mediates the relationship between TMT overseas social capital and innovation, and (4) TMT bank social capital has a moderating effect on the relationship between network position and innovation. For our overseas readers, we then present the insights from this paper in Spanish, French, Portuguese, and German.